Aid China 1937-1949 a memoir of a forgotten campaign - Clegg, Arthur (Light on China, 2003)
The China Society for People's Friendship Studies in cooperation with the Foreign Languages Press in Beijing has arranged for re-publication, in the series Light on China, some fifty books written in English between the 1860s and the founding years of the People's Republic, by journalistic and other sympathetic eyewitnesses of the revolutionary events described. Most of these books have long been out of print, but are now being brought back to life for the benefit of readers in China and abroad.